2023
DOI: 10.3390/nu15071658
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid, a Key Compound for Enhancing Sensitization to Drug in Doxorubicin-Resistant MCF-7 Cell Line

Abstract: Drug resistance is a well-known and significant obstacle in the battle against cancer, rendering chemotherapy treatments often ineffective. To improve the effectiveness of chemotherapy, researchers are exploring the use of natural molecules that can enhance its ability to kill cancer cells and limit their spread. Docosahexaenoic acid (DHA), a lipid found in marine fish, has been shown to enhance the cytotoxicity of various anti-cancer drugs in vitro and in vivo. While the combined use of chemotherapeutic drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…An in vitro investigation has demonstrated that DHA exhibits a synergistic interplay with doxorubicin in MCF7 cells, augmenting intracellular drug accumulation [130], thereby corroborating the synergistic therapeutic outcome mentioned earlier. Notably, the downregulation of Pgp and Transglutaminase 2 emerges as a putative mechanism underlying the sensitization of drug-resistant cancer cells to chemotherapy [131][132][133].…”
Section: Interactions Of N-3 Pufa With Other Antineoplastic Drugssupporting
confidence: 73%
“…An in vitro investigation has demonstrated that DHA exhibits a synergistic interplay with doxorubicin in MCF7 cells, augmenting intracellular drug accumulation [130], thereby corroborating the synergistic therapeutic outcome mentioned earlier. Notably, the downregulation of Pgp and Transglutaminase 2 emerges as a putative mechanism underlying the sensitization of drug-resistant cancer cells to chemotherapy [131][132][133].…”
Section: Interactions Of N-3 Pufa With Other Antineoplastic Drugssupporting
confidence: 73%
“…The anti-invasive activity against MDA-MB-231 cancer cells was demonstrated by the upregulation of type II cytoskeletal 1 (KRT1) proteins and keratin [ 261 ]. In addition to these apoptotic processes, ferroptosis was induced, and drug-resistant breast cancer cells’ resistance was reversed by fish-derived 37 [ 262 ]. Compound 37 has been demonstrated to increase the amount of lipid peroxides in the cellular membrane, which could contribute to oxidative stress and apoptosis [ 262 ].…”
Section: Marine Algaementioning
confidence: 99%
“…In addition to these apoptotic processes, ferroptosis was induced, and drug-resistant breast cancer cells’ resistance was reversed by fish-derived 37 [ 262 ]. Compound 37 has been demonstrated to increase the amount of lipid peroxides in the cellular membrane, which could contribute to oxidative stress and apoptosis [ 262 ]. Furthermore, when coupled with Dox as a treatment for drug-resistant carcinomas, marine-derived 37 has demonstrated a synergistic anticancer effect [ 262 ].…”
Section: Marine Algaementioning
confidence: 99%
See 1 more Smart Citation
“…Along with this, ω-3FA ingestion is associated with a lowered prevalence of inflammation [19] through the lowering of pro-inflammatory cytokines triggered by oxidative stress [20,21]. Various studies have also studied the anti-inhibitory effect of ω-3 FAs on cancers [22,23]. Over the decades various preclinical and clinical studies have been conducted using ω-3FAs to show their efficacy in reducing cardiovascular ailments.…”
Section: Introductionmentioning
confidence: 99%